2004
DOI: 10.1002/cpp.396
|View full text |Cite
|
Sign up to set email alerts
|

The aftermath of therapist–client sex: exploited women struggle with the consequences

Abstract: This study explores the ongoing experience of women who were sexually involved with their psychotherapists (therapist-client sex, TCS). Fourteen women who had been engaged in TCS were interviewed to examine the constructed meanings associated with their experiences. Respondents described themselves as having been problemsaturated, lonely, and victimized by pre-TCS sexual abuse. Many respondents resolved their TCS betrayal in subsequent therapy. For most interviewees, a significant step towards confronting thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 24 publications
1
6
0
3
Order By: Relevance
“…In der themenbezogenen Literatur wird davon ausge− gangen, dass Männer an denselben Folgen des Missbrauchs lei− den wie Frauen, dass es ihnen jedoch aufgrund ihrer Sozialisati− on schwerer fällt, sich als Opfer zu sehen [10,12]. In vielen Fällen von sexuellen Übergriffen durch Professionelle werden weder vonseiten der FolgetherapeutInnen [4] noch von− seiten der PatientInnen [3,6,31] rechtliche Schritte gegen miss− brauchende TherapeutInnen eingeleitet. Auch wenn in einigen neueren PatientInnenbefragungen der Anteil derjenigen Betrof− fenen, die rechtlich gegen die grenzverletzenden TherapeutIn− nen vorgehen, höher liegt [14,34], muss vor dem Hintergrund mehrerer Studien davon ausgegangen werden, dass viele Betrof− fene entweder nicht von der Möglichkeit der Anklageerhebung wissen [39,40] oder aus Angst vor den Belastungen des Verfah− rens davor zurückschrecken [31,39].…”
Section: Risikofaktorenunclassified
See 2 more Smart Citations
“…In der themenbezogenen Literatur wird davon ausge− gangen, dass Männer an denselben Folgen des Missbrauchs lei− den wie Frauen, dass es ihnen jedoch aufgrund ihrer Sozialisati− on schwerer fällt, sich als Opfer zu sehen [10,12]. In vielen Fällen von sexuellen Übergriffen durch Professionelle werden weder vonseiten der FolgetherapeutInnen [4] noch von− seiten der PatientInnen [3,6,31] rechtliche Schritte gegen miss− brauchende TherapeutInnen eingeleitet. Auch wenn in einigen neueren PatientInnenbefragungen der Anteil derjenigen Betrof− fenen, die rechtlich gegen die grenzverletzenden TherapeutIn− nen vorgehen, höher liegt [14,34], muss vor dem Hintergrund mehrerer Studien davon ausgegangen werden, dass viele Betrof− fene entweder nicht von der Möglichkeit der Anklageerhebung wissen [39,40] oder aus Angst vor den Belastungen des Verfah− rens davor zurückschrecken [31,39].…”
Section: Risikofaktorenunclassified
“…Auch wenn in einigen neueren PatientInnenbefragungen der Anteil derjenigen Betrof− fenen, die rechtlich gegen die grenzverletzenden TherapeutIn− nen vorgehen, höher liegt [14,34], muss vor dem Hintergrund mehrerer Studien davon ausgegangen werden, dass viele Betrof− fene entweder nicht von der Möglichkeit der Anklageerhebung wissen [39,40] oder aus Angst vor den Belastungen des Verfah− rens davor zurückschrecken [31,39]. Weiterhin gibt es Belege dafür, dass die Prozesse für die Betroffenen tatsächlich mit vie− lerlei Nachteilen und Schwierigkeiten verbunden sind [31,32,34], die sich u. a. aus der täterorientierten Ausrichtung der Strafverfahren ergeben [41].…”
Section: Risikofaktorenunclassified
See 1 more Smart Citation
“…Further, some studies focus only on relationships with current clients, whereas others include those where relationships occurred after termination of professional involvement. What is not disputed is the adverse effect of such violations on clients (Ben‐Ari & Somer, ; Somer & Nachmanil, ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of quantitative studies have examined the role of peri-traumatic dissociation in the development of PTSD (e.g., Shalev, Freedman, Peri, Brandes, & Sahar, 1997;Shalev, Peri, & Canetti, 1996) and identified it as significantly predictive of PTSD symptomatology four months following exposure to the traumatic event (Freedman, Brandes, Peri, & Shalev, 1999). Several Israeli qualitative studies have shown that peri-traumatic dissociation plays an important role in the sexual victimization of female clients by their male psychotherapists (e.g., Ben Ari & Somer, 2004;Somer & Nachmani, in press;Somer & Saadon, 1999) and in the coping of emergency room social workers vicariously traumatized during terror attacks (Peled-Avram, Ben-Yizhack, Gagin, Somer, & Buchbinder, 2004;.…”
Section: Introductionmentioning
confidence: 99%